UJI EFEKTIVITAS BEBERAPA MEDIA UNTUK PERBANYAKAN AGENS HAYATI Gliocladium sp. - Gusnawaty, HS; Taufik, Muhammad; Wahyudin, Edi (Jurnal Agroteknos, 2013)
This research was carried out in the Laboratory of Pests and Disease, Agricultural Faculty of Haluoleo University, from October to December 2012. This research was arranged in A Completely Randomized Design (CRD), with 7 treatments, namely: Gliocladium sp. in sago waste (a), Gliocladium sp. in cashew seed wastes (b), gliocladium sp. in saw dust waste (c), Gliocladium sp. in corn medium (d), Gliocladium sp. in bran medium (e), Gliocladium sp. in rice medium (f) and gliocladium sp. in rice husk waste (g). The research results showed that media used had different effectiveness. The most effective medium for Gliocladium sp. Propagation was rice bran medium, based on Gliocladium sp. growth (100%), and the number of Gliocladium sp. conidium ( 2,0 x105/g). Keywords: effectiveness, Gliocladium sp., medium, propagation